ANALISIS SOSIOLOGI KARYA SASTRA DALAM NOVEL “DIA, TANPA AKU” KARYA ESTI KINASIH: KAJIAN SOSIOLOGI PENGARANG DAN SOSIOLOGI SASTRA - Ni Made Widaswari; I Nyoman Adi Susrawan; Dewa Gede Bambang Erawan (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2022)
This research is a qualitative descriptive study that aims to analyze the study of the sociology of the author and the sociology of literature in terms of the author's social status and the sociology of literature from the reader's perspective and its social influence in the novel "Dia, Tanpa Aku" by Esti Kinasih. Data collection is done by using the method of observation, documentation and library methods. The data in this study were processed using a theory triangulation technique, which means the researcher used two or more theories to be pitted or combined. The steps in data analysis are (1) reading, studying and understanding, (2) selecting data and simplifying the data, (3) presenting the data, (4) verifying the data, and (5) concluding the data. From the results of the research, there are findings from the sociology of the author and the findings from the sociology of literature. The sociological findings of the author are found to be the relationship between the author and his work, namely the story of the author's regional atmosphere, honest nature, the author's hobby of collecting stamps, the nature of the author who helps each other and the democratic nature of the author. The findings of the sociology of literature are readers and their social influence on society, namely style (appearance), sport (sports) and social events. In all the process of policy discovery, evidence was found that the novel "Dia, Tanpa Aku" by Esti Kinasih can be used as input and useful information for the community as to the importance of sociology of literature in a literary work that must be instilled in oneself